Pengaruh Penambahan Soda Kue dan Rempah-Rempah Terhadap Karakteristik Ikan Kering Rendah Garam - Wiji Rahayu; Herpandi Herpandi; Indah Widiastuti (Jurnal FishtecH, 2018)
This study aims to determine the effect of sodium bicarbonate and spices addition on the characteristics of low salted dried fish. This research method used a randomized block design (RBD) with one treatment factor and done with three replications. The treatment used in this research were the addition of sodium bicarbonate 2.5%, turmeric 0.2%, and combination of turmeric 0.2% and chili 0.2%. The results of this research showed that treatment did not significantly affect on the value of the yield, moisture content, acid insoluble ash content, salt content, and protein content of low salted dried fish. The results of sensory analysis showed that treatment significantly affect on the appearance and aroma while the taste and texture were not significant. The best product was treated with the addition of sodium bicarbonate by 2.5% which resulted in a product with a value of yield 27.6%, water content 28.83%, acid insoluble ash content 0.32%, salt content 5.83%, and the protein content 56.27%. The results of sensory analysis showed that the value for the appearance 8.3 (whole, clean, less neatly, eradiate by type), aroma 8.3 (less aroma, without additional aroma), flavour 6.91 (very tasty, specific type, without additional flavour), and texture 8.1 (dense, compact, bending, less dried).